ANALYSIS OF USER INTEREST IN ACCOUNTING INFORMATION SYSTEM TECHNOLOGY (STUDY OF THE USE OF M-PISE APPLICATION IN VILLAGE CREDIT INSTITUTIONS) - Julianto, I Putu; Wiguna, I Gd Nandra Hary; Adnyana, I Dewa Gede Anom Jambe (Proceeding of TEAMS: The International Conference on Tourism, Economic, Accounting, Management and Social Science, 2025)
This study discusses the Analysis of User Interest in Accounting Information System Technology (Study of the Use of M-Pise Applications in Village Credit Institutions). Accounting Information Systems are the most important part of every information management need. Accounting information is directly related to financial documents and business activities. Among the LPDs in Bali, one of the LPDs that has utilized the M-Pise LPD Digital application is the LPD of Ambengan Traditional Village, located in Sukasada District, Buleleng Regency. The LPD of Ambengan Traditional Village has launched the M-Pise LPD Digital/LPD Mobile application in 2019 in conjunction with the celebration of the 30th anniversary of the LPD. The problem raised is how is the implementation of User Interest in Accounting Information System Technology (M-Pise Application) in Village Credit Institutions? The theory of this research using Technology Acceptance Model (TAM). The method used in this study is a quantitative research method. The results obtained are: 1. Perception of usefulness has a positive and significant effect on Interest in Using M-Pise LPD digital. 2. Perception of security does not have a significant effect on interest in using the M-Pise application for LPD Ambengan customers. 3. Perception of trust does not have a significant effect on interest in using the M-Pise application for LPD Ambengan customers. 4. Perception of ease has a significant positive effect on interest in using the M-Pise application for LPD Ambengan customers. This shows that the system is easy to operate according to user wishes. 5. Promotion does not have a significant effect on interest in using the M-Pise application for LPD Ambengan customers. The implication of this research is trust perception and promotion get negative results, the suggestion that can be given is for LPD in Buleleng Regency to provide counseling and also explanation to the public that the use of the M-Pise application is easy and safe. In addition, for further researchers to increase the number of research samples in order to be able to assess the influence of the variables in this study more widely.